Upaya Pencegahan Perilaku Antisosial dalam Perspektif Pendidikan Islam Melalui Layanan Bimbingan Kelompok di MTS Al Washliyah Medan Krio - Chusnul Hidayati; Ira Suryani (Cetta: Jurnal Ilmu Pendidikan, 2023)
The adolescent phase is generally considered the most sensitive time in the course of a person's life. Adolescents are particularly vulnerable to the type of negative influences that might lead to antisocial behavior, which we define as behavior that society generally disapproves of. The Islamic Guidance Counseling Organization is a community resource that facilitates open dialogue on pressing social issues, including the epidemic of antisocial behavior among young people. The aim of this study was to test methods used to reduce antisocial behaviour in young people. The authors of the study looked at antisocial behavior from a Muslim worldview. Literature research for this research is qualitative. Qualitative research and data collection in libraries use methods including in-depth interviews, careful record keeping, and careful observation. Based on the findings of this study, antisocial behavior includes actions such as breaking school rules and physically attacking classmates. Personal factors, family factors, school-related factors, and social factors all influence antisocial behavior. The school's action to overcome deviant behavior in these students is first to conduct individual counseling or approach to problematic students, carried out by the Guidance and Counseling (BK) teacher, then communicate to parents and if the student still repeats his actions, the school takes action to be given a parent notification letter (SPO).